Money vs. time: Family income, maternal labor supply, and child development - Francesco Agostinelli; Giuseppe Sorrenti (University of Zurich, Department of Economics, 2018)
We study the effect of family income and maternal hours worked on child development. Our instrumental variable analysis suggests different results for cognitive and behavioral development. An additional 1,000 USD in family income improves cognitive development by 4.4 percent of a standard deviation but has no effect on behavioral development. A yearly increase of 100 work hours negatively affects both outcomes by approximately 6 percent of a standard deviation. The quality of parental investment matters and the substitution effect (less parental time) dominates the income effect (higher earnings) when the after-tax hourly wage is below 13.50 USD. Results call for consideration of child care and minimum wage policies that foster both maternal employment and child development.
Keywords: H24; H31; I21; I38; J13; J22; 330; Child development; family income; maternal labor supply